Pengaruh E-Commerce Marketing Stimuli terhadap Trust, Customer Satisfaction, dan Customer Loyalty - Sakinah, Maraya; Heruwasto, Ignatius (Fakultas Ekonomi Universitas Samudra, 2024)
Consumer behavior conceptually begins with marketing stimuli which then ends with purchasing decisions. This research analyzes the influence of e-service quality, reputation, web design and price on trust, customer satisfaction and customer loyalty. Survey data from 370 respondents obtained through an online questionnaire was then processed using structural equation modeling (SEM). The results of this research show that e-service quality, trust, and price influence customer satisfaction. Furthermore, if e-commerce can respond to customer complaints and provide services that are personally tailored to meet customer needs, customer satisfaction will be created.